Selenite reduction and ammoniacal nitrogen removal in an aerobic granular sludge sequencing batch reactor. (15th March 2018) - Nancharaiah, Y.V.; Sarvajith, M.; Lens, P.N.L.
Abstract: Simultaneous removal of selenite and ammonium by aerobic granular sludge was investigated to develop an improved biological treatment process for selenium rich wastewaters. Aerobic granules not previously exposed to selenite were able to remove selenite by converting it to elemental selenium (Se(0)) and simultaneously remove ammonium under different conditions in batch experiments. To achieve sustainable selenite and ammonium removal, an aerobic granular sludge reactor was operated in fill-and-draw mode with a cycle of anaerobic (8 h) and aeration (15 h) phases. Almost complete removal of different initial concentrations of selenite up to 100 μM was achieved in the anaerobic phase. Ammonium removal was severely inhibited when the granules were initially exposed to 1.27 mg L −1 selenite, but ammonium and total nitrogen removal efficiencies gradually improved to 100 and 98%, respectively, under selenite-reducing conditions. Selenite loading shifted ammonium removal occurring mainly during the anaerobic phase to both the anaerobic and aeration phases. Selenite was removed from the aqueous phase by converting it to nanoparticulate Se(0), which was entrapped in the granular sludge. Scanning electron microscop-energy dispersive X-ray spectroscopy and X-ray diffraction analysis confirmed the formation of Se(0) nanospheres and their retention in the granular sludge. The effluent Se ranged from 0.02 to 0.25 mg Se L −1, while treating up to 12.7 mg L −1 selenite, which is lower as compared to previous studies on selenite removal using activated sludge or anaerobic granular sludge. This study shows that aerobic granular sludge reactors are not only capable of removing toxic selenite, but offer improved treatment of Se-rich wastewaters. Graphical abstract: Highlights: First report on sustained selenite reduction by aerobic granular sludge. Simultaneous COD, nitrogen and selenite removal by aerobic granular sludge. Efficient selenite bioreduction and better entrapment of Se (0) in AGS. Selenite reduction by AGS was associated with lower colloidal Se (0) in liquid phase. Ammonium was mainly removed through nitrogen removal via the nitrite pathway.